Association of Consuming Tap Water or Purified Water during Infancy with Irritable Bowel Syndrome in Children - Ju Hee Kim; Hey-Sung Baek; Eun Kyo Ha; Hye Ryung Cha; Seung Won Lee; Man Yong Han (MDPI AG, 2022)
Objective: The objective of this study was to analyze the effect of consuming formula powder prepared with tap water or purified water during the first 4 to 6 months of life on the subsequent development of irritable bowel syndrome (IBS). Study design and setting: A total of 917,707 children who were born in Korea between 2007 and 2008 were analyzed. All children were followed up until they lost eligibility for health care services or until 2017. Data on the water used to prepare formula powder were from questionnaires answered by the parents when the child was 4 to 6 months old. IBS was defined as two or more diagnoses of IBS after the age of 4 years. Inverse probability of treatment weighting (IPTW) using the propensity score was used to balance the two groups. The risk of IBS was evaluated using a Cox proportional hazards model. Results: After weighting, there were 73,355 children in the tap water group and 73,351 in the purified water group. The purified water group had a higher risk of IBS (HR: 1.05; 95% CI: 1.01, 1.09). This relationship was also present after the subgroup analyses of males and females and the sensitivity analysis that used different definitions of IBS. Conclusions: Drinking formula powder prepared with purified water rather than tap water during the first 4 to 6 months of age was found to be associated with IBS.